Distinct Chrna5 mutations link excessive alcohol use to types I/II vulnerability profiles and IPN GABAergic neurons - Léa Tochon; Nadia Henkous; Morgane Besson; Uwe Maskos; Vincent David (Translational Psychiatry)
Abstract Genome wide association and animal studies have implicated genetic variations in CHRNΑ5, encoding the α5 subunit-containing nicotinic acetylcholine receptors (α5*nAChRs), as a risk factor for developing alcohol use disorders (AUDs). To understand how α5*nAChR mutations may influence alcohol (EtOH) drinking behavior, we used a two-bottle choice procedure with intermittent access to alcohol in male and female transgenic mice expressing either the highly frequent human single nucleotide polymorphism (α5SNP/rs16969968) or a deletion of the Chrna5 gene (α5KO). AUDs-related preconsommatory traits (anxiety, sensation-seeking and impulsivity) were assessed with a battery of relevant tasks (elevated-plus maze, novel place preference and step-down inhibitory avoidance). The implication of the α5-expressing IPN GABAergic neurons in AUDs and related behavioral traits was verified using neurospecific lentiviral (LV)-induced reexpression of the α5 subunit in α5KOxGAD-Cre mice. Both α5SNP and α5KO mice showed over-consumption of EtOH, but displayed opposite vulnerability profiles consistent with Cloninger’s subtypes of human AUDs. α5SNP mice showed Type I-like characteristics, i.e., high anxiety, novelty avoidance, whereas α5KOs exhibited Type II-like features such as low anxiety and high impulsivity. LV re-expression of the α5 subunit in IPN GABAergic neurons restored the control of EtOH intake and improved the impulsive phenotype. We demonstrate that the SNP (rs16969968) or null mutation of Chrna5 result in increased volitional EtOH consumption but opposite effects on anxiety, novelty-seeking and impulsive-like behaviors that match Cloninger type I and II of AUDs, including sex-related variations. IPN GABAergic neurons expressing α5*nAChRs play a key role in limiting both EtOH drinking and motor impulsivity.